Patient, Injury, Assessment, and Treatment Characteristics and Return-to-Play Timelines After Sport-Related Concussion: An Investigation from the Athletic Training Practice-Based Research Network. Issue 4 (July 2019) - Valovich McLeod, Tamara C.; Kostishak, Nicholas; Anderson, Barton E.; Welch Bacon, Cailee E.; Lam, Kenneth C.
Abstract : Objectives: To describe the patient, injury, assessment and treatment characteristics, as well as return-to-play timelines and clinical findings at discharge for adolescent patients after sport-related concussion. Design: Retrospective analysis of electronic medical records. Setting: Athletic training facilities of secondary school members of the Athletic Training Practice-Based Research Network (AT-PBRN). Patients: In total, 1886 patient records were reviewed. [1204 (63.8%) male, 682 (36.2%) female, age = 15.3 ± 1.9 years, height = 169.5 ± 13.5 cm, mass = 70.3 ± 17.0 kg]. Patients were diagnosed with a concussion by an athletic trainer or team/directing physician. Interventions: None. Main Outcome Measures: Descriptive analysis of patient, injury, assessment, treatment, and participation status characteristics, as well as discharge information. Results: Injury demographic forms were completed for 1886 concussion cases. A concussion-specific evaluation form was completed for 55.9% (n = 1054) of cases. Treatment documentation was completed on 829 patients (44.0% of initial documented cases). Discharge forms were completed for 750 patients (40.0% of initial documented cases). Most cases were coded as 850.9-Concussion (85.5%, n = 642) and occurred during an in-season game (49.4%, n = 308). Time lost from competition was 24.9 ± 39.9 days. Conclusions: Most concussion cases documented in this study were not on-field emergencies, as indicated by their normal clinical examinations and the lack of immediate referral to an emergency department. However, certain aspects of the clinical examination were often not assessed during the initial evaluation. These findings describe concussion assessment and recovery in adolescents and reinforce the need for a standardized approach to concussion assessment and appropriate documentation.